2011
DOI: 10.3174/ajnr.a2805
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of 4D-CT for Parathyroid Adenomas and Hyperplasia

Abstract: BACKGROUND AND PURPOSE: 4D-CT is a novel method of multiphase CT imaging. When used to localize parathyroid adenomas and hyperplasia, this technique may allow for more robust diagnostic accuracy than traditional sonography and nuclear scintigraphy techniques. The purpose of our study is to assess the accuracy of 4D-CT for localizing pathologically proved parathyroid adenomas and hyperplasia found during surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
82
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 16 publications
(19 reference statements)
3
82
2
1
Order By: Relevance
“…The method successfully located a single affected gland with 93% accuracy. In the assessment of multiglandular disease, however, sensitivity fell to 44% but specificity was impressively, at 100% (112 (125,126), and purely endoscopic parathyroidectomy (EP) (127).…”
Section: Diagnosis and Management Of Primary Hyperparathyroidismmentioning
confidence: 99%
See 1 more Smart Citation
“…The method successfully located a single affected gland with 93% accuracy. In the assessment of multiglandular disease, however, sensitivity fell to 44% but specificity was impressively, at 100% (112 (125,126), and purely endoscopic parathyroidectomy (EP) (127).…”
Section: Diagnosis and Management Of Primary Hyperparathyroidismmentioning
confidence: 99%
“…Ultrasonography has a sensitivity of 88% and specificity of 94% but when combined with Tc--99m Sestamibi scan by SPECT-CT, the sensitivity and specificity may rise to 97 and 100%, respectively (109) (C-4). minimally invasive parathyroidectomy (MIP), which can be performed as a same-day procedure, reducing patient morbidity and costs (112) (C-4).…”
Section: Imaging Procedures and Localization Techniquesmentioning
confidence: 99%
“…[9][10][11][12][13] Multiple recent studies have indicated that 4D-CT may be especially useful for preoperative localization in patients with negative or inconclusive results on sonography and technetium Tc99m sestamibi studies, reoperative parathyroid patients, patients with mild hypercalcemia, and in patients with multigland disease. [14][15][16][17][18] However, previously published reports have predominantly evaluated cohorts with small numbers of patients and have focused on specific patient populations with strict exclusion criteria. One study with a large group of patients included only those with sporadic primary hyperparathyroidism who had a single adenoma identified by 4D-CT and were undergoing initial parathyroidectomy, excluding patients with multigland disease, prior surgery, concomitant thyroid disease, mediastinal ectopic parathyroid glands, and multiple endocrine neoplasia syndromes.…”
mentioning
confidence: 99%
“…In the present case both adenomas had very high PTH levels in their aspiration fluid. Multiphase computed tomography of the cervical region (4D-CT) has became the preferred localizing method for those patients in whom the parathyroid lesion is not detected by ultrasound or scintigraphy, as its sensitivity is high for both adenoma and hyperplasia (12). Until the issue of long-term complications of NPHPT is not completely understood, it seems reasonable to consider surgery for those patients in whom the parathyroid lesion is localized by imaging procedures or traditional operation (neck exploration) for those who have osteoporosis or renal stone disease with negative imaging.…”
Section: Discussionmentioning
confidence: 99%